2015
DOI: 10.1016/j.bbmt.2014.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Veno-Occlusive Disease of the Liver in the Absence of Elevation in Bilirubin in Pediatric Patients after Hematopoietic Stem Cell Transplantation

Abstract: Veno-occlusive disease (VOD) of the liver is a well-described and significant complication of hematopoietic stem cell transplantation (HSCT), with limited successful therapeutic options in severe cases. Prompt diagnosis and initiation of treatment is crucial to restrict the extent of disease. However, a subset of patients may not meet all current diagnostic criteria at presentation, and waiting for these to be met may delay therapy. We retrospectively reviewed 794 HSCT patients treated at our institution betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
34
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 8 publications
4
34
0
3
Order By: Relevance
“…Our results are similar to the study by Myers et al 10 who reported five patients with anicteric VOD at diagnosis, two of those remained anicteric and one of these two died. 10 Our study reconfirms the importance of not overlooking a diagnosis of VOD simply due to lack of hyperbilirubinemia. Anicteric VOD is common in children after HSCT and carries a significant morbidity and even mortality.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Our results are similar to the study by Myers et al 10 who reported five patients with anicteric VOD at diagnosis, two of those remained anicteric and one of these two died. 10 Our study reconfirms the importance of not overlooking a diagnosis of VOD simply due to lack of hyperbilirubinemia. Anicteric VOD is common in children after HSCT and carries a significant morbidity and even mortality.…”
supporting
confidence: 82%
“…Total serum bilirubin is often used as a marker for response to treatment with defibrotide, as discussed in studies by Ho et al 7 and Richardson et al 8 However some patients with VOD may not have hyperbilirubinemia but still have all the other features consistent with VOD. 9,10 In a recent study by Myers et al, 10 five patients had a bilirubin of ⩽ 2 mg/dL at the time of diagnosis of VOD and reversal of portal venous flow (PVF) by ultrasonography; two of these continued to have a bilirubin of o 2 mg/dL. 10 There have been few studies focusing specifically on anicteric VOD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Печеночная РТПХ является сегодня наиболее распространенным осложнением, ведущим к остаточным проявлениям в виде поздних эффектов, которые проявляются как поствоспалительный склероз и изменения внутри-печеночных желчных протоков [59]. В случае разви-тия ВОБ у пациента на ранних этапах после ТГСК в поздней перспективе будут отмечаться гепатомега-лия и дисфункция органа.…”
Section: желудочно-кишечный трактunclassified
“…В случае разви-тия ВОБ у пациента на ранних этапах после ТГСК в поздней перспективе будут отмечаться гепатомега-лия и дисфункция органа. К развитию ВОБ чаще всего приводит использование бусульфана, треосульфана, циклофосфамида и кармустина [59]. В определен-ных случаях у ряда пациентов может фиксироваться очаговая гиперплазия, связанная с ВОБ.…”
Section: желудочно-кишечный трактunclassified